PENYULUHAN JAJANAN SEHAT â€œDETEKSI KANDUNGAN FORMALIN DAN BORAKSâ€ - Harahap, Fatma Suryani; Atifah, Yusni; Batubara, Melvariani Syari (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2017)
The role of food additives (BTP), especially preservatives, is becoming increasingly important in line with technological advances in the production of synthetic food additives. Preservatives are used to preserve food that is easily damaged. Lately with many found food products such as tofu, meatballs, noodles and snacks of school children containing harmful chemicals that cause people to be careful in consuming these types of foods. The food is often sold in the school environment by food vendors and sold freely in the community. The majority of school food snacks (PJAS) throughout 2010 still contain hazardous chemicals. As a result of almost every year still found some schoolchildren, especially at the elementary level, experiencing food poisoning. The number of PJAS containing hazardous materials is reflected from the supervision of the Food and Drug Supervisory Agency (BPOM). In this case, devotees have provided direction and counselling about healthy snacks and simple test of snack test containing formalin and borax conducted in workshop activity. The target of this activity is the teachers and elementary school children at SDN 200201 Padangsidimpuan. The number of extension participants is 90 people consisting of teachers and students. The place of execution of activities carried out in SDN 200101 Padangsidimpuan. The implementation method used an experimental method and mentoring. With this activity is expected to provide information and hazard knowledge of chemical content in foods, especially formalin and borax to create a healthy and quality generation.Keywords: Healthy snacks, formalin, borax